Изучение морфологических признаков и засухоустойчивости видов и сортов рода Hemerocallis L. в Донецком ботаническом саду НАН Украины - Крохмаль, И.И. (Промышленная ботаника, 2002)
Morphological characteristics and phenological peculiarities of 8 species and 30 sorts of Hemerocallis L. genus have been studied. Drought-resistance of 27 Hemerocallis L. sorts have been under investigation. Basing on the examining the waterbearing of the leaves, their moisture-retentive abilities and their toleran e to withering, high drought-resistance of 10 day-lily sorts has been fixed.